Pentecostalism and Slum: Challenges for the Understanding of Everyday Religious Experiences on the Margins - Mesquita, Wania Amélia Belchior (International journal of Latin American religions, 2024)
The work approaches the limits of the concepts of Pentecostalism, considering the religious and political experiences of a Pentecostal leader residing in a slum in the city of Campos dos Goytacazes-RJ, under the control of the drug trafficking faction Terceiro Comando Puro (TCP). The location is marked by social suffering, daily violence, incarceration of residents, and food insecurity. In this context, the TCP domain prevents the existence of other religious expressions whose markers, in some situations, are considered linked to the Comando Vermelho faction. The churches occupy small spaces, autonomous with noisy ceremonies, warlike language, and significant bodily and emotional exaltation. Thus, the research focuses on Pentecostalism from the margins considering that Pentecostal experiences conform and are adjusted to local sociabilities. As a methodological possibility for this article, we propose biographical accounts as a theoretical-methodological option.